Dedications and signatures on Benito Vera’s bindings in the Rodríguez-Moñino collection of the Royal Spanish Academy - Patón García, Lorena; Carpallo Bautista, Antonio (Documenta & Instrumenta - Documenta et Instrumenta, 2026)
Antonio Rodríguez-Moñino (1910–1970) was a prominent twentieth-century bibliophile. His legacy includes 255 bindings executed by Benito Vera Vigo (1923–2009), dating from the years 1965, 1966, and 1969, in which 38 former provenances have been identified. From these, 32 dedica-tions have been selected, arranged according to the classification proposed by Professor Manuel José Pedraza and distributed into four groups: the first comprises copies bearing only a signature; the second includes dedications from the author of the work to Moñino; the third consists of dedica-tions addressed to Moñino by individuals not involved in the authorship of the works; and, finally, the fourth group encompasses dedications by third parties with no connection to the bibliophile. This analysis has made it possible to identify a circle of individuals who maintained close personal relationships with Moñino, including writers, historians, and other figures.